2016
DOI: 10.3329/bjsir.v51i3.29436
|View full text |Cite
|
Sign up to set email alerts
|

Particleboard from coir pith

Abstract: This study aimed to find out the feasibility of coir pith as a raw material for particleboard production. Considering particle size, an attempt was taken to produce resin bonded coir pith particleboard and binder-less coir pith particleboard as well. The physical and mechanical properties of the board were examined. The particleboard made from medium size particle showed the best performance in aspect of properties. The particleboards made with 16% Melamine Urea Formaldehyde (MUF) had better product quality th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Also, the effect of particle size was analyzed and showed particleboards made using the medium size particle also gave the best performance for both binderless and MUF bonded boards. This indicated that coconut pith can be used for making binderless and adhesive bonded particleboard 50,52 …”
Section: Particleboard Manufactured From Bio‐based Adhesivementioning
confidence: 99%
See 3 more Smart Citations
“…Also, the effect of particle size was analyzed and showed particleboards made using the medium size particle also gave the best performance for both binderless and MUF bonded boards. This indicated that coconut pith can be used for making binderless and adhesive bonded particleboard 50,52 …”
Section: Particleboard Manufactured From Bio‐based Adhesivementioning
confidence: 99%
“…From the results, it was deduced that citric acid influences the physical and mechanical properties of particleboards from corn stalks. 49 Ahmed et al 50 used coconut pith derived from coconut husk to produce particleboard. Coconut pith is a product of coconut husk, it consists of 70 wt% of the husk and the fiber takes up 30%.…”
Section: Characteristics Of Binders Used In Particleboard Manufacturementioning
confidence: 99%
See 2 more Smart Citations
“…In order to meet rapidly increasing production and consumption demands, the use of different raw materials is inevitable. For this purpose, many lignocellulosic raw materials have been used for the production of particleboard, including vine stems (Yeniocak et al 2014), kenaf stem (Juliana et al 2014), waste tea leaves (Batiancela et al 2014), cotton stalk (Nazerian et al 2016), flax chips (Sam-Brew and Smith 2017), corn stalk (Guler et al 2016), sunflower stalk (Klimek et al 2016), coir pith (Ahmed et al 2016), poppy husk (Küçüktüvek et al 2017), rice husk and bamboo stalk (De Melo et al 2015), tobacco stalk (Acda and Cabangon 2013), rape straw (Dziurka et al 2015), banana skins (Papadopoulos 2018), palm branches (Amirou et al 2013), and reed stems (Kord et al 2015).…”
Section: Introductionmentioning
confidence: 99%